2014
DOI: 10.1177/0898010113519010
|View full text |Cite
|
Sign up to set email alerts
|

The Cultural Relevance of Mindfulness Meditation as a Health Intervention for African Americans

Abstract: African Americans experience a disproportionate rate of stress-related health conditions compared to European Americans. Mindfulness meditation has been shown to be effective for managing stress and various stress-related health conditions. This study explored the cultural relevance of mindfulness meditation training for African Americans adults. Fifteen African American adults with past or current experience with mindfulness meditation training were interviewed. Participants felt that mindfulness meditation h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
80
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(85 citation statements)
references
References 31 publications
5
80
0
Order By: Relevance
“…In contrast, we found a significant association between non-white race and younger age and WTP in MBSR. A recent qualitative study of the impact of mindfulness meditation in 15 African American adults found that such meditation was particularly culturally relevant, but that its presentation may need to be adapted to encourage participation [30]. Furthermore, non-white populations may experience barriers to participating in MBSR, ranging from financial concerns and availability to conflicting religious ideologies and a disconnect with white teachers, which could contribute to the difference between receptivity and utilization.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, we found a significant association between non-white race and younger age and WTP in MBSR. A recent qualitative study of the impact of mindfulness meditation in 15 African American adults found that such meditation was particularly culturally relevant, but that its presentation may need to be adapted to encourage participation [30]. Furthermore, non-white populations may experience barriers to participating in MBSR, ranging from financial concerns and availability to conflicting religious ideologies and a disconnect with white teachers, which could contribute to the difference between receptivity and utilization.…”
Section: Discussionmentioning
confidence: 99%
“…Mindfulness training is an acceptable approach for AAs for stress management and may be useful for prevention of stress-related health disparities [14]. Although mindfulness interventions for weight loss in AA women have not been reported thus far, such approaches have been used in multiracial populations of patients with cancer to target improvement in inflammation and psychosocial health.…”
Section: Introductionmentioning
confidence: 99%
“…18 Their spiritual practices (eg, prayer, singing hymns) serve to strengthen this relationship with God by encouraging practitioners to be receptive to God's message by being emotionally, physically, and spiritually engulfed into the present experience of worship. 22 Thus, spirituality has been found to be a meaningful coping mechanism among African Americans. 23 pressive symptoms, increasing the risk for cognitive impairment and diagnosis of dementia.…”
Section: Influence Of Spirituality On Depression-induced Inflammationmentioning
confidence: 99%